Archaeology, heritage and society: who sets the agenda? - Bueno, Lucas de Melo Reis (2011)
This paper intends to add some points in a discussion that has increased and it’s calling more attention in Brazilian archaeology since a couple of years: the hole of archaeology and archaeologists in defining ways for political heritage management. To discuss this question we’ll present a history of Brazilian archaeology, highlighting some crucial moments of this trajectory, that were marked by juridical formulations about the heritage concept and its influence in archaeological practice. As we’ll see, despite the existence of a close connection between the entrance of archaeology in the academy and important modifications in the heritage laws, the archaeologists were, for a long time, away of the decision making process about this issue.